2019
DOI: 10.1155/2019/9060845
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Plasma Fibrinogen and Serum Albumin Score Is an Independent Prognostic Factor for Resectable Stage II-III Gastric Cancer

Abstract: Background Radical gastrectomy with D2 lymphadenectomy is recognized as the standard treatment for resectable advanced gastric cancer. Preoperative fibrinogen and albumin measurements may bring clinical benefits in terms of providing advanced notice of a poor prognosis or recurrence in patients undergoing radical resection. The aim of this study was to identify markers that are predictive of a poor prognosis prior to surgery. Methods Eight hundred forty-two consecutive patients who underwent curative radical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…ALB and TP are markers reflecting nutritional status [20]. Correlation analysis in the current study demonstrated that in lung cancer patients ANC and MPV were negatively weakly correlated with ALB and TP, respectively, which showed that the inflammatory stage of lung cancer might be related to nutritional insufficiency.…”
Section: Discussionsupporting
confidence: 51%
“…ALB and TP are markers reflecting nutritional status [20]. Correlation analysis in the current study demonstrated that in lung cancer patients ANC and MPV were negatively weakly correlated with ALB and TP, respectively, which showed that the inflammatory stage of lung cancer might be related to nutritional insufficiency.…”
Section: Discussionsupporting
confidence: 51%
“…ALB is one of the most common parameters in evaluating immunological and nutritional status, and the ALB reduction is considered to be associated with systemic inflammation affecting hepatocyte catabolism and anabolism (Carr and Guerra, 2017;Fernández et al, 2019;Yoshida et al, 2020). Low serum albumin levels may also reflect poor hepatic functional reserve, influence the patient's tolerance to operation, and result in worse prognosis (Wu et al, 2019). TL is an important parameter of immune condition and plays an important role in antitumor immunity by inducing cytotoxicity and inhibiting tumor cell growth, migration, and invasion (Sarvaria et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cachexia, as a complex and multifactorial syndrome, affects about 50%-80% of cancer patients and is related to 20%-40% of cancer deaths (Freire et al, 2019). Multiple nutritional assessment systems, including Naples Prognostic Score (NPS), Nutritional Risk Screening (NRS), body mass index (BMI), albumin (ALB), and prognostic nutritional index (PNI), have emerged with the aim of detecting and predicting the clinical outcomes of gastric cancer patients (Li et al, 2019;Wu et al, 2019;Bae, 2020;Park et al, 2020;Xiong et al, 2020). It is also reported that immunological status is associated with the patient's prognosis (Sato et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have demonstrated the potentials of various types of systemic inflammatory factors as markers for predicting prognosis of malignancies (16)(17)(18)(19)(20). Inflammation, malnutrition, and immune status are factors that affect tumor development and are closely related to the prognosis of gastric cancer patients (21). However, the long-term outcome of using combinations of systemic inflammatory factors detected in peripheral blood to predict lymph node metastasis and tumor prognosis in patients with gastric cancer has not been previously addressed in studies.…”
Section: Discussionmentioning
confidence: 99%